CaMKII and reactive oxygen species contribute to early reperfusion arrhythmias, but oxidation of CaMKIIδ at methionines 281/282 is not a determining factor. (February 2023) - Haugsten Hansen, Marie; Sadredini, Mani; Hasic, Almira; Anderson, Mark E.; Sjaastad, Ivar; Korseberg Stokke, Mathis
Abstract: Background: Available evidence suggest that Ca 2+ /calmodulin-dependent protein kinase type IIδ (CaMKIIδ) and reactive oxygen species (ROS) are important in early ischemia-reperfusion arrhythmias (IRA). Since ROS can activate CaMKIIδ by oxidation of two methionines at positions 281/282, oxidized-CaMKIIδ (Ox-CaMKIIδ) has been proposed to be important for IRA. However, direct evidence for this is missing. Methods: We exposed Langendorff-perfused hearts and ventricular cardiomyocytes from C57BL/6 mice to global and simulated ischemia, respectively, and recorded arrhythmic events during early reperfusion. Hearts were collected for immunoblotting of key phosphoproteins. We evaluated the effects of beta-adrenoceptor stimulation, inhibition of CaMKII, and reduced ROS levels with isoprenaline, KN93/AIP and N -acetylcysteine (NAC), respectively. We further tested the importance of Ox-CaMKIIδ by using hearts and cardiomyocytes from mice with CaMKIIδ resistant to oxidation of methionines 281 and 282 (MMVV). Results: Hearts treated with KN93, AIP or NAC had lower incidence of early IRA, and NAC-treated cardiomyocytes had lower incidence of arrhythmogenic events. However, hearts from MMVV mice had a similar incidence of early IRA to wild type mice (WT), and MMVV and WT cardiomyocytes had a similar frequency of Ca 2+ waves and Ca 2+ sparks. Immunoblotting confirmed high levels of oxidation in early reperfusion, but revealed no significant differences in the phosphorylation levels of Ca 2+ -handling proteins in MMVV and WT hearts. Conclusions: Although CaMKII and ROS both contribute to early IRA, hearts from mice with CaMKII resistant to oxidation at methionines 281/282 were not protected from such arrhythmias, suggesting that oxidation at these sites is not a determining factor. Graphical abstract: Unlabelled Image Highlights: Arrhythmias complicate the early reperfusion phase after myocardial infarction. CaMKII oxidation is proposed to play an important role, but direct tests are missing. CaMKII inhibition and antioxidant therapy reduced reperfusion arrhythmias ex vivo. Antioxidant therapy reduced arrhythmogenic events during reperfusion in vitro. Genetic ablation of CaMKII oxidation at methionines 281/282 was not protective.